CAPABILITY-BASED PERSPECTIVE TO COMPETITIVE ADVANTAGES OF THE FIRM: THEORETICAL REVIEW AND EMPIRICAL EVIDENCES FROM US AND JAPANESE CORPORATE FIRMS - Dinh, Thi Thanh Binh (Journal of International Economics and Management, 2018)
This paper reviews the theory of competitive advantages of the firm from the capabilitybased perspective. This perspective is originated from the resource-based one. It inherits the resource-based perspective in the respect that it focuses on the exploitation of firm-specific assets (core competence) that are difficult if not impossible to imitate, but complements the explanation of how firms renew competences to response to shifts in business environment. Within the framework of capability-based perspective, the competitive advantages of the firm is firstly specified from its coordination mechanisms and incentive mechanisms, then moved to organizational learning processes, and then capabilities and competences. We have demonstrated this framework via the cases of the evolution of US corporations and Japanese corporations from various sources of empirical literatures.